Tumour stage and implementation of standardised cancer patient pathways: a comparative cohort study - Jensen, Henry (Br J Gen Pract, 2016)
BACKGROUND: Some European countries have introduced standardised cancer patient pathways (CPPs), including urgent referrals, with the aim of diagnosing cancer at an earlier stage. This is despite a lack of evidence, particularly in patients with symptomatic cancer diagnosed via general practice. AIM: To compare tumour stages in patients with incident cancer diagnosed via general practice before, during, and after CPP implementation in Denmark in 2008–2009. DESIGN AND SETTING: A comparative cohort study of data from GPs and registries on patients with incident cancer listed with a GP before (n = 1420), during (n = 5272), and after (n = 2988) CPP implementation. METHOD: χ(2) test was used to compare stage distributions and logistic regression to estimate odds ratios (OR) of having local cancer after versus before CPP implementation. RESULTS: Distribution of tumour stages did not differ statistically significantly across time (P = 0.494) or between CPP use (P = 0.202). For all cancers combined, the OR of having local cancer after CPP implementation was 0.88 (95% confidence interval [CI] = 0.73 to 1.06) compared with before. For CPP-referred patients, the OR of having local cancer was 0.77 (95% CI = 0.62 to 0.94) compared with all patients before CPP implementation; the corresponding OR for non-CPP-referred patients was 0.96 (95% CI = 0.80 to 1.14). CONCLUSION: No clear tendencies were observed confirming earlier detection of cancer after rather than before CPP implementation. CPP-referred patients had lower odds of having local cancer after CPP implementation than all patients before CPP implementation; this could be because the GPs refer patients who are ‘more ill’ as urgent referrals.